PROFESSIONAL SEMINAR "BASIS OF PROFESSIONALISM OF TEACHER OF GENERAL SECONDARY EDUCATION INSTITUTION" IN DUAL EDUCATION SYSTEM OF MASTERS "SECONDARY EDUCATION (MATHEMATICS)" SPECIALTY - Олександр Школьний (Фізико-математична освіта)
Formulation of the problem. In modern economic conditions, the vast majority of master students of specialty "Secondary Education (Mathematics)" in NPU named after M.P. Dragomanov is in a situation of forced "duality" of their education. As a result, there are difficulties with the organization of the learning process of such students, as well as the quality of their assimilation of the material of the educational program. It seems natural to transfer such students to the dual form of education. This will solve a significant part of the mentioned organizational and methodological problems. Dual education requires fundamentally new forms of learning organization. An important element in its structure is the professional seminar "Basis of professionalism of teacher of general secondary education institution." This seminar is designed to quickly respond to current problems of young teachers that arise in the process of adapting to working conditions at school.